Understanding Young Adults’ Mental Health Information-Seeking on Social Media: A Qualitative Exploration - Augustin Mustika Chairil; Syifa Syarifah Alamiyah; Arina Himatul Husna (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2026)
Along with the rapid growth of social media, information related to mental health is increasingly presented in various forms of content. Social media has transformed into a medium that facilitates users, particularly young adults, in seeking mental health information. By using the concept of information search patterns, the algorithms and the role of social media as a platform, this article analyzes patterns of mental health information seeking among young adults and illustrates how they access social media. Through focus group discussions (FGDs) and in-depth interviews with health stakeholders, this article explores how young adults use social media to seek mental health information, which is largely driven by visually appealing content and often followed by self-diagnosis. Algorithms indirectly shape patterns of mental health content consumption, and content produced by government platforms frequently fails to appear within the algorithmic filters encountered by young adults. This condition poses a challenge for stakeholders in delivering digital literacy, particularly in mental health information content.